Habitat Suitability of Javan Gibbon in Gunung Salak, West Java (Kesesuaian Habitat Owa Jawa di Gunung Salak, Jawa Barat) - Wim Ikbal; Lilik Budi Prasetyo; Idung Risdiyanto (Jurnal Manajemen Hutan Tropika, 2008)
Objective of this study was to provide spatial information of Javan gibbon habitat suitability and distribution in Gunung (Mt.) Salak area for Management Authority of Mt. Halimun-Salak National Park. Informations on Javan gibbon distribution was collected through a number of survey during December 2005–June 2006 in Kawah Ratu (Parakan Salak, Sukabumi), Pondok Wisata Cangkuang (Cidahu, Sukabumi), and Bobojong Village (Bogor). Twenty two groups were identified using direct count and triangle count method from over 47 identified positions. Habitat suitability was formulated based on10 ecogeographical variables (criteria), consisting of forest type (primary forest, secondary forest, low-land forest, and submontane forest), slope (0–15%, 15–45%, >45%), and distance to non-forested land, river/water body, and road/tracks. The result showed that Mt. Salak consisted of 13.20% (17.53 km2), 26.25% (34.86 km2), 19.40% (25.77 km2), 4.16% (5.53 km2), and 20.17% (26.78 km2) of high-suitable, suitable, moderate suitable, less and low suitable level subsequently, and 12.69 km2 or 9.56% was not suitable for Javan gibbon habitat. It was also revealed that that 3 and 9 groups were living in high suitable and suitable habitat respectively; 13 groups in moderate suitable, while for each less and low suitable habitat, 2 Javan gibbon groups lived in.